Metal partitioning after in situ filtration at deep-sea vents of the Lucky Strike hydrothermal field (EMSO-Azores, Mid-Atlantic Ridge, 37°N). (March 2020) - Cotte, L.; Chavagnac, V.; Pelleter, E.; Laës-Huon, A.; Cathalot, C.; Dulaquais, G.; Riso, R.D.; Sarradin, P.-M.; Waeles, M.
Abstract: Metal partitioning between the dissolved and particulate phases is still poorly constrained within the early mixing of hydrothermal fluids and deep seawater. In this study, in situ filtration has been used to collect early buoyant plume fluids. This has provided the unique opportunity to reassess precisely metal partitioning along the mixing gradient by limiting chemical exchange processes between the dissolved (<0.45 μm) and particulate (>0.45 μm) phases during sampling. We report on the partitioning of three major metals (Fe, Cu, Zn) in the early buoyant plume of six black and clear smokers from the Lucky Strike hydrothermal field (37°N, MAR; EMSO-Azores deep sea observatory). We show that chemical changes are limited in the warmest part of the plume [50–150°C, dMn > 40 μM; dilution factor (DF) of 1–10 by NADW] as metal partitioning displays a chemical signature similar to the end-member one. However, as the dilution ratio between the hydrothermal fluid and North-Atlantic Deep-water (NADW) increases (4–50°C, dMn < 40 μM; DF of 10–100 by NADW), metal partitioning is affected by different precipitation and oxidation processes. Molar ratios normalized to Fe in the particles highlight the onset of Fe oxides formation, the precipitation of barite and the decreasing contribution of sulfide minerals (mainly Cu–Fe sulfides and sphalerite/wurtzite) along with fluid dilution. Graphical abstract: Image 1 Highlights: Metal fate in early buoyant plumes of deep sea vents is poorly constrained. In-situ filtration indicates that chemical changes for Cu, Zn and Fe are limited. The main sulfide mineral phases precipitate before venting. The onset of Fe oxides formation occurs at high dilution.